Inter-Islamic Law Simulation in Education as an Effort to Build a Community Legal Culture - Naser Ali Abdulghani; Sarkanto; Wahyudin Khairul Sya'ban (Yayasan Azhar Amanaa Yogyakarta, 2026)
The purpose of this article is to analyze the implications of inter-law simulation in education on the formation of a community's legal culture. The writing method used is normative juridical research with a conceptual and sociological approach, supported by a literature study of laws and regulations, legal theories, and relevant scientific literature. The results of the study show that inter-law simulation in education is able to increase students' legal awareness through direct experience in applying legal norms, social, Islamic legal values and cultural values contextually. This approach not only strengthens cognitive legal understanding, but also forms sustainable law-abiding attitudes and behaviors, thus contributing significantly to strengthening the legal culture of society.